Best practices for Core Argo floats - Part 2: physical handling, deployment and metadata considerations - Morris, Tamaryn; Scanderbeg, Megan; West-Mack, Deborah; Gourcuff, Claire; Poffa, Noé; Udaya Bhaskar, Tata V. S.; Hanstein, Craig; Diggs, Steve; Talley, Lynne; Turpin, Victor; Liu, Zenghong; Owens, Breck (Frontiers in Marine Science, 2024)
Following on from Part 1: Best Practices for Core Argo floats -Getting started and data considerations, we present Part 2: Best Practices for Core Argo floats in terms of physical handling and deployments and recommended metadata parameters. The objective is to encourage new and developing scientists, research teams and institutions to contribute to the OneArgo Program through increased deployments regionally, specifically to the Core Argo mission. Only by leveraging sustained contributions of current Core Argo float groups with new and emerging Argo teams and users, can the OneArgo initiative be realized. This paper makes involvement with the Core Argo mission smoother by providing a framework endorsed by a wide community for these observations.